Development of a new method to promote tooth extraction socket healing through immediate transplantation of extracted dental pulp tissue - An in vivo study - Kohei Ijichi; Reiko Tokuyama-Toda; Mai Takeshita-Umehara; Toshio Yudo; Yusuke Takebe; Kazuhito Satomura (PLoS ONE, 2025)
In tooth extraction sockets, natural healing is usually expected; however, early healing is advantageous for subsequent treatment and leads to improvement in the patient’s quality of life. In recent years, it has been found that dental pulp tissue contains several dental pulp stem cells. The main objective of this study was to verify whether immediate transplantation of dental pulp tissue without any culture process into the extraction socket would promote healing of the socket. To verify this, the rat’s bilateral maxillary second molars were extracted simultaneously, and dental pulp tissue was collected from the extracted teeth. The right extraction socket was immediately transplanted with dental pulp tissue, and the left extraction socket was used as a control. Both sockets were then covered with immediate curing resin. Micro-CT was performed over time, up to 28 days after tooth extraction, bone mineral content was measured, and histological examination was performed. As a result, inflammatory bone resorption had a normal course in both groups after tooth extraction, but bone resorption tended to be suppressed on the 3 days after tooth extraction in the transplant group. In the transplant group, compared to the control group, the radiopaque area increased from the 5 days after tooth extraction onward, and a significant difference was observed on the 7 days after tooth extraction. Furthermore, bone mineral content measurements suggested that bone maturation progressed from earlier in the transplant group, and histological examination confirmed that bone healing was promoted in the transplant group. These findings confirmed that immediate transplantation of dental pulp tissue can promote bone healing in the extraction socket and suggested that this method can be useful as a new method to promote healing in the extraction socket.